MODEL OF SPREAD BACTERIAL RESISTANCE IN HOSPITAL - RIZKA (NIM: 20116011), NELA
Antibiotic resistance is the ability of bacteria to avoid or inhibit attacks from antibiotics. The phenomenon of the spread antibiotic resistance has increased significantly, especially in hospitals. The negative impacts arising from these phenomena include the high treatment cost and high mortality rates of patients due to infectious disease. In response to these problems, this thesis proposed a model of spread bacterial resistance in hospitals. Since antibiotic treatment is most commonly used to treat infections, antibiotics therapy remain formulated in the model. From analysis of model, we obtained that the spread of bacterial resistance in the hospital, at the end, still occur even though the patient get antibiotics therapy. Meanwhile, if the patientÃ‚Â’s level of awareness to keep themselves from resistant bacterial contamination is considered, then the spread of resistance in the hospital can be controlled. The higher the level of patient awareness the smaller the spread of resistance occurs.